2018
DOI: 10.1177/2054358118803322
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Education and Shared Decision Making in the Chronic Kidney Disease Population: A Narrative Review

Abstract: Purpose of review:Provision of education to inform decision making for renal replacement therapy (RRT) is a key component in the management of chronic kidney disease (CKD), yet patients report suboptimal satisfaction with the process of selecting a dialysis modality. Our purpose is to review the influencers of RRT decision making in the CKD population, which will better inform the process of shared decision making between clinicians and patients.Sources of information:PubMed and Google Scholar.Methods:A narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 84 publications
(228 reference statements)
0
50
0
1
Order By: Relevance
“…Through our narrative review, we have also found that patient-important outcomes are underreported and that incorporating patients into the research process itself can help inform methodology to incorporate the patient perspective. 51 We have taken this novel approach with the involvement of M.S., a patient on dialysis, which we believe has enriched our findings through the prioritization of CKD patients’ lived experiences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Through our narrative review, we have also found that patient-important outcomes are underreported and that incorporating patients into the research process itself can help inform methodology to incorporate the patient perspective. 51 We have taken this novel approach with the involvement of M.S., a patient on dialysis, which we believe has enriched our findings through the prioritization of CKD patients’ lived experiences.…”
Section: Discussionmentioning
confidence: 96%
“…We have recently reviewed the influencers of renal replacement decision making and found that comprehensive education programs through multidisciplinary teams are vital to overcoming educational barriers and bringing about shared decision making. 51 A standardized CKD education plan that is delivered in an individualized manner should be the ultimate goal in predialysis CKD management. Through our narrative review, we have also found that patient-important outcomes are underreported and that incorporating patients into the research process itself can help inform methodology to incorporate the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that there is a need for more interactive patient education. However, the desired education modalities of patients with renal disease are currently unknown [ 38 ]. We would suggest that web-based sources should offer more assessment modes because these are crucial to evaluating knowledge and can assist patients by providing insight into their personal goals [ 21 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a protocol for a scoping review on the information available for SDM with older patients with AKD considering their treatment options has been published 41. Finally, numerous narrative reviews and overview papers on these topics in the context of kidney failure have been published as well 42–63. All of these papers are either limited to a single aspect of the decision-making process or their methodological framework limits their validity due to uncertainties in the generalisability and reproducibility of the reported findings.…”
Section: Introductionmentioning
confidence: 99%